The Prevalence of Unsafe Behaviors in Iranian Workers: A Sys-tematic Review and Meta-Analysis - Mahdi MALAKOUTIKHAH; Hadiseh RABIEI; Soheil HASSANIPOUR; Mehdi JAHANGIRI (Tehran University of Medical Sciences, 2021)
Background: Unsafe behaviors are the cause of 80% of accidents. However, there has also been no worldwide review and meta-analysis of the prevalence of workers' unsafe behaviors. Therefore, the present study aimed to investigate and estimate the prevalence of unsafe behaviors among Iranian workers using a systematic review and meta-analysis study. Methods: This systematic review and meta-analysis were conducted from Nov to Dec 2018. The researchers searched Medline/PubMed, Scopus, Embase, Science Direct, and Google Scholar for international articles and four Iranian databases (Scientific Information Database, MagIran, IranMedex, and IranDoc) for Persian articles. The method of reporting this study was based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) checklist. Results: Overall, 235 articles from databases were imported to EndNote library. Final screening of the included studies produced a total of 38 studies. Based on the random-effect model, the prevalence of total unsafe behaviors, non-use or inappropriate use of personal protective equipment, and inappropriate work posture was 40.37% (CI 95% = 35.8-44.9), 27.79% (CI 95% = 21.2-34.3), and 14.87% (CI 95% = 10.7-18.9). There was no statistically significant relationship between unsafe behaviors and mean age, mean of work experiences, and year of study. Conclusion: The prevalence of unsafe behaviors among Iranian workers was relatively high and the most common behaviors were non-use or inappropriate use of PPE; one of the most important causes for this behavior is lack of training, inappropriate working conditions, and lack of positive attitude towards safety. Therefore, further studied are required to investigate the causes of these unsafe behaviors.